Long-term monitoring reveals the effect of precipitation and silviculture on Nothofagus regeneration in Northern Patagonia mixed forests - Sola, Georgina Giselle (2024)
Background Tree regeneration is a key component of resilience because it promotes post-disturbance recovery of forests. Northwestern Patagonia from Argentina is occupied by Nothofagus alpina (Na), N. obliqua (No), and N. dombeyi (Nd) forests that grow along an intense precipitation gradient, managed throughout shelterwood silvicultural system by technicians of the Lanin Natural Reserve. The objective of this study was to evaluate the infuence of seeding cuttings over the dynamics of Nothofagus mixed forests across landscape (precipitation gradient) based mainly on the composition and abundance of tree regeneration, permanent sampling plots and generalized linear mixed models. In particular, we analysed: (i) the structure of sexual and asexual regeneration during<10, 10–20 and>20 years after harvest (the dynamics of managed forests), and (ii) the structure of sexual regeneration in primary and managed forests after>20 years of harvest (the efect of silviculture). Results Nd was the most abundant species in the regeneration of managed forests during all periods in both sites despite its lower contribution to the adult cohort. During the 10–20 years period after harvest, the humid site exhibited higher regeneration density than the mesic site (120,000 and 6000 ind ha−1, respectively), and it decreased afterwards. The number of established regeneration (>2 m height) was lower for Na in the mesic site and for No in the humid site (0 and 57 ind ha−1, respectively). However, in comparison to No, Na showed a higher number of sprouted stumps and sprouts per stump, and a higher sprout height in the mesic site. No exhibited higher sprout mortality in the humid site. Finally, the regeneration of primary forests showed lower density and height, and a more balanced composition than that of managed forests. Conclusions The silvicultural efects on the mixed forest regeneration dynamics was strongly infuenced by the condition of sites. Therefore, management prescriptions should be adjusted in order to consider the environmental variation occurring through the entire landscape. An adaptive management that considers the pattern and process of sexual and asexual regeneration and disturbance will contribute to promote a greater resilience of mixed forest ecosystems.